The Saint of the Time of the Plague—Szymon of Lipnica OFM († 1482) and his Liber Miraculorum: An Example of the Late-Medieval Polish Collection of Miracles - Starzynski, Marcin (Journal of medieval religious cultures, 2023)
Simon of Lipnica, who died in 1482, was counted among the blessed in 1685, has been a saint of the Catholic Church since 2007, and was a Franciscan Observant associated with the priory founded by Johannes of Capestrano in the suburb of Krakow, is one of the not fully recognized figures building the image of Polish religious culture. After his death, a "miracle office" was established in the Bernardine priory, where miraculous events through the intercession of Simon were recorded meticulously on an ongoing basis. In this way, the largest Polish late-medieval collection de miraculis was created. Drawing from the new critical edition, this article presents this monument not only in the context of the first years of Simon's "miracle office" but also in the context of the development of the miraculum as a literary genre.